BUILDING A RELIGIOUS CULTURE IN SCHOOL ENVIRONMENT - Umi Nasikhah; Zulkifli; Nurudin (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
Many studies have proven that the function of educational institutions is not only to produce intellectual generations, but also to become a place to instill good values in the form of morals in order to answer the needs of society about their children's education to counteract the various influences of today's changes. This paper will try to describe the culture of character building and religious morals in the school environment. To answer the purpose of this study, the writer tries to review various literature related to education, especially the formation of religious moral character in the environment. The data collection process begins with data search, continues with analysis, evaluates and organizes the data into information that is ready to be compiled into a draft before being reviewed to see the suitability of the theme of this study based on the validity and reliability of the findings. The results of this review are efforts that can be made by an educational institution, including by building and shaping a religious culture in schools. The strategy for the formation of religious culture in schools can be done through a power strategy, persuasive strategy, and normative re-educative with exemplary approaches, habituation, reward and punishment and persuasive approaches. With this we can conclude that the religious culture developed in schools is an effort to form school members who have al-Karimah morals as the goal of national education, namely developing the potential of students to have religious spiritual strength and noble morals.